Abundant Extractable Metabolites from Temperate Tree Barks: The Specific Antimicrobial Activity of Prunus Avium Extracts - Amin Abedini; Marius Colin; Jane Hubert; Emilie Charpentier; Apostolis Angelis; Heithem Bounasri; Benjamin Bertaux; Alexis Kotland; Fany Reffuveille; Jean-Marc Nuzillard; Jean-Hugues Renault; Sophie C. Gangloff (MDPI AG, 2020)
Tree barks are mainly considered as wood wastes from forestry activities, but represent valuable resources as they may contain antimicrobial compounds. Here, we aimed to evaluate the possible antimicrobial activities of bark extracts and to characterize the chemical composition of the most active extract. Ten methanol bark extracts were tested in vitro against 17 bacterial strains and 5 yeast strains, through minimum inhibitory concentration (MIC) and minimum bactericidal (or fungicidal) concentration (MBC/MFC) assays. The extract from Prunus avium (E2-4) displayed the largest bactericidal activity against Gram-positive bacteria, with a lethal effect on 6 out of 8 strains. Antibiofilm assays of E2-4 were performed by crystal violet staining and enumeration of adhered bacteria. Assays demonstrated a biofilm inhibitory effect of E2-4 against Staphylococcus aureus CIP 53.154 at concentrations equal to or higher than 250 µg/mL. Chemical profiling of E2-4 by 13C nuclear magnetic resonance (NMR) revealed the presence of dihydrowogonin as a major constituent of the extract. E2-4 was fractionated by centrifugal partition chromatography and the three fractions containing dihydrowogonin were tested for their antibacterial and antibiofilm activities, revealing similar activities to those of E2-4. Dihydrowogonin was positively assessed as an interesting antimicrobial compound, which could be valued from wastes of Prunus avium barks.